Corrigendum: Redescription of Nemachilichthys rueppelli, a senior synonym of N. shimogensis (Teleostei: Nemacheilidae) - Keskar, Ashwini; Kumkar, Pradeep; Katwate, Unmesh; Ali, Anvar; Raghavan, Rajeev; Dahanukar, Neelesh (Zootaxa, 2016)
In Keskar et al. (2015) we emended the original name Cobitis rupelli Sykes, 1839, because Sykes (1839) specifically mentions that the species was named after Rüppell. The specific epithet ‘rupelli’, with a single ‘p’, is an incorrect original spelling and should be emended into ‘ruppelli’ as required by Article 32.5 (International Commission on Zoological Nomenclature, 1999). However, citing Art 32.5.2.1, we also suggested that because Sykes (1839) named the species after Rüppell, the umlaut ‘ü’ should be corrected to ‘ue’ and that the specific epithet should thus be ‘rueppelli’. This is an error. Sykes (1839) did not use ‘ü’ in the original spelling of the species epithet rupelli: hence changing it to ‘ue’ is incorrect. Therefore, the correct spelling for the species should be ‘Nemachilichthys ruppelli’, a change that should be reflected in the title and in the rest of the text of Keskar et al. (2015).